2019
DOI: 10.3892/mmr.2019.9980
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4 inhibits the proliferation and osteogenic potential of fibroblasts from ankylosing spondylitis via the Wnt/β‑catenin pathway

Abstract: Ankylosing spondylitis (AS) is an autoimmune condition characterized by chronic inflammation and abnormal ossification as the primary features of the disease. The aim of the present study was to investigate the role of C-X-C chemokine receptor type 4 (CXCR4) in ossification from patients with AS. CXCR4 expression was assessed by western blot analysis and immunohistochemistry analysis of tissues obtained from patients with AS and controls. Fibroblasts were isolated, cultured and incubated with AMD 3100 and stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…β-catenin is a critical protein in the classical Wnt signaling pathway that plays a central role in the formation of ectopic bone (10). Moreover, the production of β-catenin is positively associated with AS osteogenesis (60). The present study revealed that β-catenin levels were upregulated in the AS model (PG) and downregulated in the groups with a reduced mechanical load (PG + NLB and PG + PLB), which was consistent with previous studies (10).…”
Section: Discussionsupporting
confidence: 91%
“…β-catenin is a critical protein in the classical Wnt signaling pathway that plays a central role in the formation of ectopic bone (10). Moreover, the production of β-catenin is positively associated with AS osteogenesis (60). The present study revealed that β-catenin levels were upregulated in the AS model (PG) and downregulated in the groups with a reduced mechanical load (PG + NLB and PG + PLB), which was consistent with previous studies (10).…”
Section: Discussionsupporting
confidence: 91%
“…The expression of the CXCL12/CXCR4 axis was increasing in the patients with SCI and AS (Knerlich-Lukoschus et al, 2011;Tysseling et al, 2011). Besides, a study found that CXCR4 could accelerate the ossification of fibroblasts in patients with AS (He et al, 2019). FN1 (fibronectin 1) is involved in the process of cell adhesion and migration (Cai et al, 2018) and could rely on the TGF-β/PI3K/Akt pathway to promote chondrocyte differentiation and collagen production in fractured bones (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 encodes a CXC chemokine receptor specific for stromal cell-derived factor-1 located on the cell surface, which acts with the CD4 protein to support HIV entry into cells; it is also highly expressed in breast cancer cells (36). He et al (37) discovered that inhibition of CXCR4 prevents the proliferation and osteogenic potential of fibroblasts from ankylosing spondylitis, indicating that CXCR4 may play a key role in the development and perpetuation of joint stiffness. Our results were consistent with these previous reports.…”
Section: Discussionmentioning
confidence: 99%